THE ROLE OF THE INDUSTRY OF KASHKADARYA REGION IN THE SOCIO-ECONOMIC DEVELOPMENT OF THE REPUBLIC - Rustamov Alisher Bahodirovich (Scholar Express Journals, 2022)
The experience of developed countries shows that the highest share of value added in the creation of gross domestic product and the role of industry as a key industry in providing employment is growing. Recently, the industry has become a leading industry in our country in terms of these indicators. That is, the role of industry in the socio-economic development of the country is of particular importance. Therefore, the further development of industry, especially the development of science-based proposals and recommendations for the sustainable development of regional industries, is one of the most pressing issues today. This article highlights the role of industry in socioeconomic development, the role of industry in the country, and provides a statistical analysis of its current state
Keywords: Digital economy; forecast values eviews package; trend models; investment